Is the Nectar Sugar Content the Key to Improving Onion and Bunching Onion Seed Yield? - Soto Vargas, Verónica Carolina; Gonzalez, Roxana Elizabeth; Caselles, Cristian A.; Galmarini, Claudio Romulo (MDPI, 2023)
Bunching onion as well as onion show great variability in seed yield among cultivars. Understanding the role of floral rewards and attractants to pollinator species is crucial to improving crop seed yield. Nectar sugar concentration is one of the most important factors affecting bee–flower interaction. The objective of this work was to determine the differences in nectar sugar composition between onion and bunching onion lines grown in the same location during two consecutive cultivation cycles and in two different productive areas under open field conditions, and the relationship of these sugars with seed yield. The results obtained showed that, regardless of the season and the location, bunching onion produced higher seed yields than onion, and the sugar content was always higher than in onion. Fructose represented on average 56% of the total sugars, glucose 34% and, sucrose 9% of the total amount of sugars in nectar. There were differences between the two locations studied. Fructose content had a significant correlation with seed yield. The amount of sugars in bunching onion could be the reason why this species does not have pollination problems in contrast to onion plants. In addition, the differences found in seed yield between locations could provide options for seed companies to make production decisions.